Studies on the antidiabetic effects of Mangifera indica stem-barks and leaves on nondiabetic, type 1 and type 2 diabetic model rats - Amrita Bhowmik; Liakot Ali Khan; Masfida Akhter; Begum Rokeya (Bangladesh Pharmacological Society, 2009)
Mangifera indica Linn, locally known as mango tree has been claimed to possess antidiabetic properties by many investigators. The present study was undertaken to screen the hypoglycemic and antihyperglycemic activity of both ethanol and water extracts of leaves and stem-barks of M. indica in nondiabetic and diabetic model rats in different prandial state. The results showed that all of the extracts had significant antihyperglycemic effect in type 2 diabetic model rats when fed simultaneously with glucose load (p<0.05-0.01; p<0.005-0.001). Moreover, the ethanol extract of stem-barks showed significant antihyperglycemic effect when the extract was fed 30 min prior to the glucose load (p<0.01). Investigations were carried out to evaluate the effect of M. indica on glucose absorption using a rat intestinal preparation in situ. The ethanol extracts of stem-barks reduced glucose absorption gradually during the whole perfusion period in type 2 diabetic rats.